A values-based approach to knowledge in the public's representations of climate change on social media - Fage-Butler, Antoinette (Frontiers in Communication, 2022)
This paper supports recent calls for research programs that explore the public’s online representations of their knowledge of science-related topics, and argues that a useful line of inquiry in such a program would be to investigate how values are communicated in the public’s construction of their knowledge of climate change on social media. A values-based approach to public knowledge broadens the concept of knowledge from being a cognitive and quantifiable attribute that the public may be expected to have less of than experts. In so doing, it captures more holistic aspects of public epistemologies, and acknowledges that climate change is an emotive and normative issue. This paper connects such a future line of inquiry with the concept of the public’s climate “imaginaries” and proposes a number of qualitative methods for analysing the public’s communication of knowledge/values on social media.